Evaluation of containment and mitigation strategies for an influenza A pandemic in China. (May 2015) - Weng, Wenguo; Ni, Shunjiang
The world is still in heightened awareness of the potential threat of another influenza pandemic, although it has been 5 years since the 2009 influenza A (H1N1) pandemic. Evaluation of the adopted intervention strategies for handling the 2009 H1N1 pandemic is helpful for dealing with future outbreaks. In this paper we developed a hybrid model combining meta-population and agent-based models to evaluate the containment and mitigation strategies (e.g., contact tracing and quarantine of contacts at assembly sites in the early phase, more medical institutions to detect cases and treat serious patients in the developing phase, and rapid vaccines delivered to students first) for an H1N1 pandemic that were adopted in China. We find that the presented model can retrospectively fit relatively well to the spreading progress through comparison of the simulation results with actual infections data, and it can be used for practical application in evaluating the containment and mitigation strategies for an influenza pandemic if model validation and parameter estimation can be conducted by using actual data. The results will contribute to understanding the spread of viruses and the control of infectious diseases, and to helping government officials create policies on handling an influenza pandemic, especially beneficial to a large and diverse country such as the People's Republic of China.